Pengembangan Aplikasi Pelatihan Bahasa Pada Tunarungu Menggunakan Google Speech Berbasis Android - M. Brilian Misbah Al Hakim; Herman Tolle; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Deaf children belong to a group of children who experience language and communication problems because of their inability to get a voice. Despite their shortcomings they still have the potential to learn to speak and speak. In developing language skills and speaking deaf children need special services in the form of systematic language teaching to minimize the impact caused by the phlegm they experience. In this study developing language teaching and training services using Android-based mobile devices technology by utilizing Google Speech to process sound. Language training applications for Deaf provide a feature to facilitate deaf people in practicing language skills. In the application there are pictures and learning videos that discuss pronunciation pronunciation techniques and techniques to support training and learning. Based on the validation testing that has been done, the results obtained with a percentage of 100%, which means the system has met functional requirements. As for the usability level, the results of the average test are 70.5, with the user acceptance rate stated in the Acceptable, grade C category with a Good rating.